Research on product detection and recognition methods for intelligent vending machines - Jianqiao Xu; Zhifeng Chen; Wei Fu (Frontiers in Neuroscience, 2023)
With the continuous development of China's economy and the improvement of residents' living standards, it also brings increasing costs of labor and rent. In addition, the impact of the pandemic on the entity industry has brought opportunities for the development of new retail models. Based on the booming development of artificial intelligence, big data, and mobile payment in the new era, the new retail industry using artificial intelligence technology has shown outstanding performance in the market. Among them, intelligent vending machines have emerged in the new retail model. In order to provide users with a good shopping experience, the product detection speed and accuracy of intelligent vending machines must be high enough. We adopt Faster R-CNN, a mature object detection algorithm in deep learning, to solve the commodity settlement scenario of intelligent vending machines.